Survivin’ acute myeloid leukaemia—a personalised target for inv(16) patients - Greiner, Jochen; Brown, Elliott; Bullinger, Lars; Hills, Robert K.; Morris, Vanessa; Döhner, Hartmut; Mills, Ken I.; Guinn, Barbara Ann (International Journal of Molecular Sciences, 2021)
Abstract: Despite recent advances in therapies including immunotherapy, patients with acute myeloid leukaemia (AML) still experience relatively poor survival rates. The Inhibition of Apoptosis (IAP) family member, survivin, also known by its gene and protein name, Baculoviral IAP Repeat Containing 5 (BIRC5), remains one of the most frequently expressed antigens across AML subtypes. To better understand its potential to act as a target for immunotherapy and a biomarker for AML survival, we examined the protein and pathways that BIRC5 interacts with using the Kyoto Encyclopedia of Genes and Genomes (KEGG), search tool for recurring instances of neighbouring genes (STRING), WEB-based Gene Set Analysis Toolkit, Bloodspot and performed a comprehensive literature review. We then analysed data from gene expression studies. These included 312 AML samples in the Microarray Innovations In Leukemia (MILE) dataset. We found a trend between above median levels of BIRC5 being associated with improved overall survival (OS) but this did not reach statistical significance (p = 0.077, Log-Rank). There was some evidence of a beneficial effect in adjusted analyses where above median levels of BIRC5 were shown to be associated with improved OS (p = 0.001) including in Core Binding Factor (CBF) patients (p = 0.03). Above median levels of BIRC5 transcript were associated with improved relapse free survival (p < 0.0001). Utilisation of a second large cDNA microarray dataset including 306 AML cases, again showed no correlation between BIRC5 levels and OS, but high expression levels of BIRC5 correlated with worse survival in inv(16) patients (p = 0.077) which was highly significant when datasets A and B were combined (p = 0.001). In addition, decreased BIRC5 expression was associated with better clinical outcome (p = 0.004) in AML patients exhibiting CBF mainly due to patients with inv(16) (p = 0.007). This study has shown that BIRC5 expression plays a role in the survival of AML patients, this association is not apparent when we examine CBF patients as a cohort, but when those with inv(16) independently indicating that those patients with inv(16) would provide interesting candidates for immunotherapies that target BIRC5.
Keywords: BIRC5; Overall survival; Survivin; Acute myeloid leukaemia; Core Binding Factor (CBF); Inv(16)